Feelings of guilt attributed by women with aids compared with their disease - Carolina Maria de Lima Carvalho; Marli Teresinha Gimeniz Galvão (Rev Rene)
This article aimed to understand the feelings of guilt that women with AIDS attributed as they face their disease. This is a qualitative study, mediated by thematic oral history. A total of ten women with AIDS in Fortaleza-CE participated in the research. There was an interview recorded for the collection of data, whose results were categorized after transcription and texting. The results show different ways of blaming for the infection, from the discovery of the diagnosis to the time they live with the disease. These relate to the professional environment, to themselves and to their sexual partner. It was evidenced the importance of addressing and understanding the feelings of guilt experienced and faced by women with AIDS facing the illness. So, moved by the theme, the nurses might reflect about a more human-oriented practice, also to meet the emotional needs of the patients.